Pharmacokinetics and clinical efficacy of midazolam in children with severe malaria and convulsions. - Muchohi, SN; Kokwaro, G; Ogutu, B; Edwards, G; Ward, SA; Newton, C (2008)
AIM: To investigate the pharmacokinetics and clinical efficacy of intravenous (IV), intramuscular (IM) and buccal midazolam (MDZ) in children with severe falciparum malaria and convulsions. METHODS: Thirty-three children with severe malaria and convulsions lasting > or =5 min were given a single dose of MDZ (0.3 mg kg(-1)) IV (n = 13), IM (n = 12) or via the buccal route (n = 8). Blood samples were collected over 6 h post-dose for determination of plasma MDZ and 1'-hydroxymidazolam concentrations. Plasma concentration-time data were fitted using pharmacokinetic models. RESULTS: Median (range) MDZ C(max) of 481 (258-616), 253 (96-696) and 186 (64-394) ng ml(-1) were attained within a median (range) t(max) of 10 (5-15), 15 (5-60) and 10 (5-40) min, following IV, IM and buccal administration, respectively. Mean (95% confidence interval) of the pharmacokinetic parameters were: AUC(0,infinity) 596 (327, 865), 608 (353, 864) and 518 (294, 741) ng ml(-1) h; V(d) 0.85 l kg(-1); clearance 14.4 ml min(-1) kg(-1), elimination half-life 1.22 (0.65, 1.8) h, respectively. A single dose of MDZ terminated convulsions in all (100%), 9/12 (75%) and 5/8 (63%) children following IV, IM and buccal administration. Four children (one in the IV, one in the IM and two in the buccal groups) had respiratory depression. CONCLUSIONS: Administration of MDZ at the currently recommended dose resulted in rapid achievement of therapeutic MDZ concentrations. Although IM and buccal administration of MDZ may be more practical in peripheral healthcare facilities, the efficacy appears to be poorer at the dose used, and a different dosage regimen might improve the efficacy.